Studi Kelayakan Bisnis Pada Brand Baju Muslim Sabhira_co - Agus Sutardi; Anggini Hardiyanti; Intan Yulia Azzahra; Rosa Amelia; Hilman Al Hafizh; Azamni Dhohirudin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Fashion Sabhira is a business that grew from a reseller business to a distributor with a unique history. Sabhira was established on August 28, 2016 first operating as a reseller and distributor who takes goods from others. When the shop in Andir became very popular, Sabhira decided to open her own shop on Jln. Bengawan, Bandung. started to build its own brand with the name "Sabhira". The research method that we do is using a qualitative method by interviewing the company Sabhira_coShabira is a Brand Fashion business that is in demand by the Muslim community. The high demand in the market makes the opportunities of Sabhira's business very promising, both among women and men. The establishment of this Sabhira business will have a special impact on the economic structure of the community in the Sabhira business establishment environment, this can be seen from the increase in employee income. Where the average worker's income will increase with the salary he receives plus the bonuses given if the number of consumers who buy is more than the usual amount over time. Shabira is a Fashion Brand business that is in demand by the Muslim community. The high demand in the market makes the opportunities of Sabhira's business very promising, both among women and men. In the preparation of this business feasibility study report using 6 aspects.